2022
DOI: 10.4103/aja202261
|View full text |Cite
|
Sign up to set email alerts
|

Genetically predicted insomnia causally increases the risk of erectile dysfunction

Abstract: Sleep has attracted extensive attention due to its significance in health. However, its association with erectile dysfunction (ED) is insufficiently investigated. To investigate the potential causal links between sleep traits (insomnia, sleep duration, and chronotype) and ED, this study was performed. The single-nucleotide polymorphisms (SNPs) associated with insomnia, sleep duration, and chronotype were retrieved from previous genome-wide association studies (GWAS). A conventional two-sample Mendelian randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Therefore, to prevent ED, we recommend giving up cigarette and alcohol consumption. In line with previous observational studies and MR analyses, we also report a significant association between insomnia, snoring, and ED [43] , [44] , [45] . Clinicians should recognize and treat sleep disorders in the general population, especially in patients with ED.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, to prevent ED, we recommend giving up cigarette and alcohol consumption. In line with previous observational studies and MR analyses, we also report a significant association between insomnia, snoring, and ED [43] , [44] , [45] . Clinicians should recognize and treat sleep disorders in the general population, especially in patients with ED.…”
Section: Discussionsupporting
confidence: 92%
“…32,33 Snoring and insomnia were also shown, in previous MR studies, to contribute to the development of ED, but in view of the high data overlap, they were excluded in the confounders. 34,35 With adjustment for confounders, our MVMR further revealed that the casual effects of genetic susceptibility to IS on ED were not mediated by relevant screening confounders, as compared with CHD and HF. Thus, physicians should pay more attention to ED progression in patients with IS.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, it is necessary to include confounders in MVMR analysis (both the recognized risk factors and diseases recently proven by MR studies, such as T2D, dyslipidaemia, obesity, smoking, and COVID‐19) 32,33 . Snoring and insomnia were also shown, in previous MR studies, to contribute to the development of ED, but in view of the high data overlap, they were excluded in the confounders 34,35 . With adjustment for confounders, our MVMR further revealed that the casual effects of genetic susceptibility to IS on ED were not mediated by relevant screening confounders, as compared with CHD and HF.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, we excluded palindromic SNPs with ambiguous minor allele frequencies falling outside the range of >0.45– < 0.55, as well as incompatible allele combinations from different individuals at two or more loci, to ensure the integrity of the dataset ( 25 ). We also calculated the F statistic, F = beta^2/SE^2, to assess the strength of the IVs, excluding those with corresponding F-statistic values below 10 as weak IVs ( 26 ). Additionally, we performed leave-one-out sensitivity analysis, excluding one SNP at a time and conducting IVW analysis on the remaining SNPs to exclude specific SNPs driving significant effects ( 27 ).…”
Section: Methodsmentioning
confidence: 99%